KARAKTERISTIK PERJANJIAN KREDIT PENSIUN PADA PT. BANK TABUNGAN PENSIUNAN NASIONAL TBK KANTOR CABANG PEMBANTU BINJAI - Ayu Pratiwi (Universitas Harapan Medan, 2020)
Retirement is one of government’s policies on employees, based on their age. Article 239, Paragraph 2 of PP (Government Regulation) No. 11/2017 states that “(2) Age limit for retirement as it is specified in paragraph 1, a. 58 years old for administrative employees, ahli muda functional employees, ahli muda functional employees, and skilled functional employees, b. 60 years old for higher manager and madya functional officials, and 65 years old for ahli madya (top managers). Most of the government employees face various mental, economic, and sosial problems approaching their retirement period. They fee that their annuity is not adequate to meet their needs in retirement so that some of them borrow maney from BTPN. The research used judicial empirical method with descriptive qualitative approach which was aimed to describe or describe existing facts relating to the Characteristics of the Pension Credit Agreement at PT. National Pension Savings Bank Tbk Binjai Sub-Branch Office. By using data sources from primary data and secondary data, secondary data consisting of primary, secondary and tertiary legal materials through library research which is analyzed qualitatively. The Pension Credit Agreement is an anonymous agreement (onbenoemd overeenkomst) which is made in writing in standard form and is made under hand so that it does not have perfect proof in front of the court. Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking contradicts article 28i paragraph 2 of the 1945 Constitution of the Republic of Indonesia of the second amendment and is against the principle of balance, so that the legal consequence of this imbalance is making an Agreement This pension credit is faulty at the beginning of the juridical period, so it needs to be revised.